Aboriginal Practitioners Offer Culturally Safe and Responsive CBT: Response to Commentaries. (2nd January 2014) - Nelson, Jeff; Ryan, Kelleigh; Rotumah, Darlene; Bennett‐Levy, James; Budden, Wayne; Stirling, Janelle; Wilson, Shawn; Beale, Dean
<x xml:space="preserve">Abstract</x> We appreciate the valuable commentaries that have been provided for our paper "Can CBT be effective for Aboriginal Australians? Perspectives of Aboriginal practitioners trained in CBT." The international authors identify how CBT, with adaptations by culturally responsive practitioners can be of value for non‐Western and Indigenous peoples. The commentary by Australian psychologists Dudgeon and Kelly questions the value of CBT for Indigenous Australians, terming it a "Western therapy" that is "culturally unresponsive" and "culturally blind." They also critique the methodology of the study. We argue that CBT can be adapted by culturally competent practitioners to be culturally safe in Australia, as elsewhere. Cultural safety is mostly a function of the therapist, not the therapy. In the Bennett‐Levy et al. (2014) study, CBT was delivered in a culturally responsive way by Aboriginal counsellors within their own communities. CBT is a particularly adaptable and versatile therapy, and embodies principles of empowerment and self‐determination that are central to Indigenous social and emotional well‐being. We are concerned that CBT, which has strong empirical support and has been adapted elsewhere for a range of cultures, including Indigenous cultures, may be being denied to Indigenous Australian clients. There is considerable opportunity to evaluate the effectiveness and versatility of CBT, and variations of its mode of delivery, for all Australians.